Electrical Resistivity Method to Characterize Collapsibility of Gypseous Soil - Arwa F. Dheyab; Farouk M. Muhauwiss (Migration Letters, 2023)
Arid and semi-arid regions have had many gypseous soils. Due of its unpredictable moisture response, it is one of the most difficult soils. Gypsum, a moderately soluble salt, can affect soil engineering qualities, and changes in water content can cause fast soil fabric collapse, harming adjacent structures. These deposits are metastable. Geotechnical qualities are critical to civil engineering design and construction. Traditional site research methods included drilling and excavation to assess geotechnical parameters. The methods were limited by cost, time, and data coverage. Continuous soil subsurface resistivity profiles can be obtained quickly and non-destructively using electric resistivity. The objective of this study is to investigate an electrical resistivity approach for characterizing collapsibility features in gypseous soils. To achieve this, disturbed gypseous soil samples were taken from Salah-Aldeen Governorate, Iraq. The laboratory measured the electrical resistance of gypseous soils with 4-16% water content and 75-95% compaction ratios using a Miller 400 D resistivity meter. Results showed that electrical resistivity vs. pressure curves followed similar trends as e vs. logp curves in dry conditions but not in soaked conditions.